How is ice cream made? - Hansen, Grace (2018)
This title will go through the process of how ice cream is made. It will begin at the dairy farms where cows are milked. It will then follow the milk to the creamery, and then from the creamery to the ice cream factory. Aligned to Common Core Standards and correlated to state standards. Abdo Kids Jumbo is an imprint of Abdo Kids, a division of ABDO.--
Includes index.
Ages 4-7
Keywords: Ice cream, ices, etc -- Juvenile literature; Ice cream industry -- Juvenile literature; Ice cream, ices, etc; Ice cream industry; Ice cream, ices, etc; Ice cream industry; Ice cream industry; Ice cream, ices, etc; Juvenile works; Juvenile works